VARIOUS ASPECTS OF PAREMIOLOGICAL UNITS - Zhulduz, Rsaliyeva; Zhankara, Dadebayev; Ali, Nor Liza Binti Haji (PEOPLE: International Journal of Social Sciences, 2019)
The objective of the research is the study of the structure and semantics of the English paremiological units (on the material of the thematic group "labour-idleness"). The following tasks are set and solved in the article: to give a definition to the term “paremiological unit”; to identify different aspects of the paremiological units which is belong to the branch of the linguistics, paremiology. The expected results of the doctoral thesis will contribute to the development of the theory of linguistics, paremiology, linguistic folklore, comparative linguistics and linguoculture. The results of the research will find application for conducting scientific courses and seminars, in the process of reading lectures and special courses in English language.